(3eNJUQ bhGYO GdRQcTis - (3YHO GdhgGH Hf CMeO Hf Ydj GdnMnfaj, fSHg Edi eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO , J (B973 (3g`s ((3eUQ GdeMQhSI s)
(3ChdgG (B:s
(3CeG HYO agPg bhGYO YXjeI EfJNHJgG ef cJGH GdbhGYO ddTjN HOQ GdOjf GdRQcTi hQJHJg Ydi MQha GdeYLe JSgjdkG ddWGdH hGYde Cf GSe Gdabg jTJed Ydi CfhGY EMOgG eYQaI CMcGe GdMhGOK s
(3BNQgG (B:s
(3Ch GdeVWQ Edi JfGhd GdNeQ dG JHGM dge hEf YXeJ GdeTbI hGddg JYGdi CYde hdjcf Pdc BNQ GdbhGYO GdefJNHI gi bhGYO GdRQcTi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1359s
Keywords: (3CUhd Gdabgs